Medical waste management: a review - Akter, Nasima (BRAC Research and Evaluation Division (RED), 2019)
A review of medical waste management systems was performed to understand (a) the various handling and disposal procedures in different countries. (b) the knowledge and awareness of individuals involved in medical waste generation. handling and disposal, and (c) the potential impacts of the waste stream on both human health and the natural environment. The purpose of the study is to provide direction for further study. Information was collected mainly from literature review and online search. It was found that a variety of methods were used by the medical facilities to dispose their wastes including burning, burial. entombing, selling, dumping, and removal by municipal bins. The waste disposal practice was found to be quite unsafe. and both clinical and non-clinical wastes were found to be thrown together. There was insufficient awareness of the magnitude of the medical wastes issue by concerned individuals at different levels from director or divisional head to tokai (waste pickers). One study (Akter et al. 1998) showed that the hospital staff including high officials. and waste "haulers" were not aware of the safe disposal and handling of hospital waste. Laboratory analysis showed severe contamination of infectious wastes to the environment. Children. adults. and animals all have the potential to come into contact with these wast.es which may pose severe health risks to them. There was no safety measure observed in dealing with waste disposal or laboratory analysis of infectious or hazardous diseases. The chemicals used for the staining and preservation of slides and for the sterilization and cleaning of equipment and surroundings are potentially harmful to the laboratory technician and the environment. Hospital wastes pose a significant impact on health and environment. From this study it can be said that there is an urgent need for raising awareness and education on medical waste issues. Proper waste management strategy is needed to ensure health and environmental safety. For further study, it is needed to collect more information on impacts. disposal and management to draw a clear conclusion. Need to collect information and examples from developed country or the country, which has sound medical waste management system. Find alternatives and appropriate technologies for developing countries. Need extensive study on this medical waste and its management aspects as well.